Accelerometry‐Derived Physical Activity of First Through Third Grade Children During the Segmented School Day. (12th September 2016) - Weaver, R. Glenn; Crimarco, Anthony; Brusseau, Timothy A.; Webster, Collin A.; Burns, Ryan D.; Hannon, James C.
ABSTRACT: BACKGROUND: Schools should provide children 30 minutes/day of moderate‐to‐vigorous‐physical‐activity (MVPA). Determining school day segments that contribute to children's MVPA can inform school‐based activity promotion. The purpose of this paper was to identify the proportion of children accumulating 30 minutes/day of school‐based MVPA, and to identify school day segments' contribution to children's MVPA. METHODS: First‐third graders (N = 323 [173 girls and 150 boys]) accelerometer‐derived sedentary behaviors, light activity, and MVPA were measured for 1 to 5 school days. Children's activity was estimated during class time, lunch, physical education (PE), and recess. To explore disparities in MVPA, children were stratified into high/low‐active groups. RESULTS: Girls and boys accumulated 30.4 and 34.4 minutes/day of MVPA on PE days and 23.5 and 27.3 minutes/day of MVPA on non‐PE days. This translated to 36.5 and 44.1% of girls and boys accumulating 30 minutes of MVPA on PE days and 16.3 and 36.5% on non‐PE days. On PE days, PE contributed the most MVPA for girls and boys (11.8 and 13.0 minutes/day), followed by class time (11.4 and 12.5 minutes/day), recess (5.2 and 6.5 minutes/day), and lunch (2.0 and 2.4 minutes/day). Disparities between high/low children were greatest during PE and class time. CONCLUSIONS: Most children were not accumulating 30 minutes/day of MVPA. PE and class time are promising school day segments for promoting MVPA.